A single crystalline porphyrinic titanium metal–organic framework - Yuan, Shuai (Royal Society of Chemistry, 2015)

(untitled) (Chem Sci)
We successfully assembled the photocatalytic titanium-oxo cluster and photosensitizing porphyrinic linker into a metal–organic framework (MOF), namely PCN-22. A preformed titanium-oxo carboxylate cluster is adopted as the starting material to judiciously control the MOF growth process to afford single crystals. This synthetic method is useful to obtain highly crystalline titanium MOFs, which has been a daunting challenge in this field. Moreover, PCN-22 demonstrated permanent porosity and photocatalytic activities toward alcohol oxidation.